Self-Healing dalam Lirik Lagu Evaluasi karya Hindia : Analisis Tazkiyatun Nafs dalam Tasawuf - Alya Raysha Davira; Muhammad Nabil Sabitul A; Dadan Firdaus (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Mental health has become one of the most discussed issues among young people who face social pressure, achievement demands, and the complexities of modern life. Such conditions often lead to emotional exhaustion and encourage individuals to seek personal recovery through self-healing. One artistic medium that reflects this experience is the song Evaluasi by Hindia, which portrays self-reflection, emotional struggle, and efforts toward recovery. This study aims to analyze the representation of self-healing in the lyrics of Evaluasi and to examine its relevance to the concept of tazkiyatun nafs in Islamic mysticism. The object of this study is the lyrics of Evaluasi from Hindia’s album Menari dengan Bayangan (2019). The study employs Stuart Hall’s theory of representation, John I. Saeed’s semantic theory, Kristin Neff’s concept of self-compassion, and the concept of tazkiyatun nafs as developed by Al-Ghazali and Ibn Qayyim al-Jawziyyah, especially amradh al-qulub, takhalli, tahalli, and tajalli. This research uses a qualitative approach with qualitative content analysis. Data were collected through documentation and analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings show that the lyrics of Evaluasi represent emotional vulnerability, mental exhaustion, and social pressure, which can be interpreted in line with the concept of amradh al-qulub. In addition, the self-healing process represented in the lyrics reflects the stages of tazkiyatun nafs: takhalli, tahalli, and tajalli. Semantic analysis also reveals that the diction and expressions in the song construct meanings related to self-reflection, self-acceptance, resilience, and hope. Thus, Evaluasi functions not only as a musical work, but also as a medium that represents psychological recovery and spiritual transformation.